2018
DOI: 10.1155/2018/4835823
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nasal Obstructive Disorders on Sinonasal Symptoms in Children with Different Levels of Bronchial Asthma Control

Abstract: Allergic rhinitis (AR) and allergic rhinosinusitis (ARS) are typical upper airway pathologies (UAP) in children with bronchial asthma (BA) frequently accompanied with nasal obstructive diseases (NOD). In order to establish the effect of NOD on correlations between nasal and synonasal symptoms with clinical assessments of asthma control, 82 children, 9.8 [8.9; 10.7] years old, with atopic BA were assessed using ACQ-5 for the BA control level, TNSS for nasal symptoms, and SNOT-20 for synonasal quality of life in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
0
8
0
1
Order By: Relevance
“…In particular, in the study of Chen et al [ 9 ], the AARM method was used to study nasal patency in children with asthma and nasal symptoms, but patients with anatomical deformations of upper airways were excluded from the study cohort. At the same time, according to our data, up to 50% of children with asthma and nasal symptoms have such deformations [ 2 , 7 ]. Motomura et al [ 19 ] demonstrated that, for patients with asthma, a decrease in nasal airflow is characteristic, but the effect of the comorbid UAP on the respiratory function of the nose was not considered.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…In particular, in the study of Chen et al [ 9 ], the AARM method was used to study nasal patency in children with asthma and nasal symptoms, but patients with anatomical deformations of upper airways were excluded from the study cohort. At the same time, according to our data, up to 50% of children with asthma and nasal symptoms have such deformations [ 2 , 7 ]. Motomura et al [ 19 ] demonstrated that, for patients with asthma, a decrease in nasal airflow is characteristic, but the effect of the comorbid UAP on the respiratory function of the nose was not considered.…”
Section: Introductionmentioning
confidence: 89%
“…AR as well as allergic rhinosinusitis may contribute to worsening asthma control and complicating diagnostic and therapeutic management of asthmatic patients, especially in severe asthma [ 5 ]. AR in asthmatics children often combines with other upper airway pathologies (UAP), in particular, with nasal obstructive disorders (NOD) which includes hypertrophy of the pharyngeal tonsil (HPT) and/or anomalies of intranasal structures (AINS) [ 3 , 6 , 7 ]. UAP have a negative effect on the course of asthma requiring timely, objective monitoring of the basic physiological functions involved in the pathological process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, it was previously demonstrated that AR may occur in all children with atopic BA who have nasal symptoms ( 19 ), which is consistent with the results reported in Blaiss ( 20 ). The use of modern imaging methods enabled to identify anomalies of intranasal structures, hypertrophic changes in the pharyngeal tonsil, and debuting hypertrophy of the nasal mucosa in a significant fraction of children with atopic BA ( 12 , 13 , 19 ). This indicates that the processes of remodeling of the extracellular matrix are involved in the formation of pathological changes in the respiratory tract in these patients ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…One of the reasons for the insufficient level of BA control is the negative impact of comorbidities on the course of BA, primarily upper respiratory tract (URT) pathologies, including allergic rhinitis (AR) and allergic rhinosinusitis (ARS) (9)(10)(11)(12)(13)(14). IgE-mediated inflammation of the nasal mucosa within the structures of the ostiomeatal complex leads to impairment of mucociliary transport, drainage of mucus from the paranasal sinuses, as well as to ventilation disorders (15,16).…”
Section: Introductionmentioning
confidence: 99%